(untitled) (African Journal of Biomedical Research, 2021)
Prostate cancer (PCa) is the number one cancer in both incidences and mortality among men in Africa including Nigeria. Evidence suggest that African men present with more advanced disease, suggesting that they are highly unscreened group for PCa. This study examined the risk perception and uptake of PCa screening among civil servants in Oyo state secretariat. This was a descriptive cross-sectional survey of 192 male staff of Oyo State Secretariat, selected by simple random sampling technique. Respondents’ risk perception and uptake of prostate cancer screening were examined using a structured questionnaire. Pearson’s chi-square and correlation coefficient were used to test hypotheses at 0.05 level of significance. Mean age of respondents was 47.44±5.36 years. Up to 140(73.3%) of respondents were aware of PCa, mainly through literature (29.5%), 53.8% had good knowledge of PCa. However, 78% perceived themselves not at risk for prostate cancer. For 39.6%, prostate cancer is a myth. While only 15(7.9%) had ever been screened, a greater percentage (92.1%) had never been screened. There is significant association between knowledge and uptake of prostate cancer screening (χ2=3.748, p=0.05) as well as between perception of susceptibility and uptake of prostate cancer screening (χ2=26.093, p=0.00). The risk perception for Prostate Cancer is low among the study cohort. There is need for more public enlightenment to improve awareness and uptake of prostate cancer screening services.